Runt-Related Transcription Factor 3 Promotes Acute Myeloid Leukemia Progression - Zhang, Wenwen; Ma, Qian; Long, Bing; Sun, Zhangyi; Liu, Lingling; Lin, Dongjun; Zhao, Minyi (Frontiers in Oncology, 2021)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy with a high relapse/refractory rate. Genetic and epigenetic abnormalities are driving factors for leukemogenesis. RUNX1 and RUNX2 from the Runt-related transcription factor (RUNX) family played important roles in AML pathogenesis. However, the relationship between RUNX3 and AML remains unclear. Here, we found that RUNX3 was a super-enhancer-associated gene and highly expressed in AML cells. TCGA database showed high expression of RUNX3 correlated to poor prognosis of AML patients. We observed Runx3 knock-down significantly inhibited leukemia progression by inducing cell cycle arrest, DNA damage, and apoptosis in murine AML cells. By ChIP-seq analysis, we discovered RUNX3 in AML cells bound more genes involved in cell cycle, DNA-damage repair, anti-apoptosis pathways compared to that in normal bone marrow cells. Runx3 knock-down obviously inhibited the expression of these genes in AML cells. Overall, we identified RUNX3 as an oncogene overexpressed in AML cells and Runx3 knock-down suppressed AML progression by inducing cell cycle arrest, DNA damage, and apoptosis.